The correlation between the coaptation height of mitral valve and mitral regurgitation after mitral valve repair - Dan Wei; Jie Han; Haibo Zhang; Yan Li; Chunlei Xu; Xu Meng (Journal of Cardiothoracic Surgery, 2017)
Abstract Background To investigate the association between the coaptation height of mitral valve and mitral regurgitation after mitral valve repair. Methods From Sep 2014 to Jun 2015, 20 patients underwent mitral valve valvuloplasty for mitral regurgitation were included. Ring annuloplasty was performed in all cases. Mitral valve short-axis dimension (MVd), coaptation height (CH), Left ventricular ejection fraction (LVEF) were measured by the transesophageal echocardiography before the operation in operation room and 3 months and 12 months after the operation by the transthoracic echocardiography. A degree from 0 to 4 was used to measure the degree of mitral regurgitation. Results There were 14 patients with 0, 3 patients with 1, 3 patients with 2 of mitral regurgitation 12 months after the operation. CH (3.53 ± 1.91 mm) increased significantly at 3 months (5.05 ± 1.09 mm) and 12 months after operation (5.22 ± 1.15 mm) (p < 0.05). MVd and LVEF were not significantly changed after mitral valve repair. Furthermore, CH after resuscitation have a statistically significant negative correlation with the degree of mitral regurgitation 12 months after operation. Conclusion The mitral valve repair with mitral valve ring induce the morphologic change of the mitral valve structure. The increase of CH after mitral valve repair may be one of the main factors in regulation of mitral regurgitation.